2015
DOI: 10.1155/2015/462182
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Central Programmed Movement Pattern by Temporal Electrical Stimulation-Assisted Training in Patients with Spinal Cerebellar Atrophy

Abstract: Disrupted triphasic electromyography (EMG) patterns of agonist and antagonist muscle pairs during fast goal-directed movements have been found in patients with hypermetria. Since peripheral electrical stimulation (ES) and motor training may modulate motor cortical excitability through plasticity mechanisms, we aimed to investigate whether temporal ES-assisted movement training could influence premovement cortical excitability and alleviate hypermetria in patients with spinal cerebellar ataxia (SCA). The EMG of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Instead, it lets gravity force much-assisting muscle force in producing arm movements. Next we further demonstrate this by characterizing the temporal organisation of agonist/antagonist muscular activation, which is the most basic and widely used descriptor of muscle patterns (Berardelli et al, 1996; Chiovetto et al, 2010; Cooke and Brown, 1994; Corcos et al, 1989; David et al, 2016; Forgaard et al, 2013; Huang et al, 2015; Irlbacher et al, 2006).…”
Section: Resultsmentioning
confidence: 90%
“…Instead, it lets gravity force much-assisting muscle force in producing arm movements. Next we further demonstrate this by characterizing the temporal organisation of agonist/antagonist muscular activation, which is the most basic and widely used descriptor of muscle patterns (Berardelli et al, 1996; Chiovetto et al, 2010; Cooke and Brown, 1994; Corcos et al, 1989; David et al, 2016; Forgaard et al, 2013; Huang et al, 2015; Irlbacher et al, 2006).…”
Section: Resultsmentioning
confidence: 90%
“…However, these results need to be confirmed in a large sample of patients and a consensus is missing on the parameters of stimulation that need to be used. Another option which remains to be explored is the use of electrical stimulation to assist the antagonist muscle and modify the relative timing of agonist/antagonist bursts [154].…”
Section: Mario Manto Hiroshi Mitomamentioning
confidence: 99%
“…One of the most basic and widely used descriptor of muscle commands is the tri-phasic burst pattern. Decades of research have consistently shown that, during point-to-point movements, muscle activations follow a tri-phasic temporal organization (Corcos et al, 1989; Cooke and Brown, 1994; Berardelli et al, 1996; Chiovetto et al, 2010; Forgaard et al, 2013; Huang et al, 2015; David et al, 2016). A first agonist burst produces the body-limb acceleration.…”
Section: Introductionmentioning
confidence: 99%